A Tetragonal Natrolite. - Andersen, E. Krogh; Danø, M.; Petersen, O. V. (Meddelelser om Grønland, 1969)
Tetragonal natrolite has been found as white or, less frequently as, dull pink micro-crystalline aggregates in hydrothermal veins in naujaite, at two separate localities in Ilímaussaq. The aggregates are built up of sheaf-like groups of prismatic crystals, the greatest dimension of which is about 0.01 mm. The single crystals are bounded by a single prism and either a basal pinacoid or a bipyramid. The density is 2.210 ± 0.002. The mineral is uniaxial, optically positive. nε = 1.493 ± 0.001 , nω = 1.480 ± 0.001. DTA and TGA curves of both ordinary natrolite and tetragonal natrolite are presented ; tetragonal natrolite dehydrates at a slightly lower temperature than ordinary natrolite. The mineral is tetragonal, space group probably 142d. The unit cell dimensions are: a0 = 13.043 ± 0.001 Å, c0 = 6.619 ± 0.001 Å, and Vol. = 2252 Å3 . The chemical composition of the mineral falls within the range of composition of natrolites as reported in the literature.